AB 55. Epithelial - myoepithelial carcinoma of the trachea - Cheva, Aggeliki (Pioneer Bioscience Publishing Company, 2012)
BACKGROUND: Presentation of a case of an epithelial - myoepithelial tumour with an unusual location. PATIENTS AND METHODS: We report a case of a 34-year-old man who was presented to our hospital with vigorous cough and dyspnoea. The patient’s chest X-ray showed a stem lesion with protrusion in trachea. Histological examination revealed neoplasm formed by biphasic cell population arranged by an inner layer of duct-forming epithelial cells and an outer layer of myoepithelial cells over a fibrous, mucinous stroma. The epithelial - myoepithelial dualism was confirmed using immunohistochemical methods: the epithelial cells were positive for Ck7 and Ck8/18; the myoepithelial cells were positive for S-100 protein, SMA and p63. Expression of proliferation index Ki-67 was particularly low. RESULTS: The above morphological and immunohistochemical results are compatible with the diagnosis of an epithelial - myoepithelial carcinoma of the trachea. CONCLUSIONS: Epithelial - myoepithelial carcinoma is a low-grade malignant tumour. According to literature, most commonly occurs in salivary glands, particularly in parotic gland, but it can also occur in unusual locations such as breast, lachrymal gland, nose, paranasal sinus, lung, bronchus and, as in our case, trachea.